1999
DOI: 10.1159/000030384
|View full text |Cite
|
Sign up to set email alerts
|

Renal Metastasis from Prostatic Adenocarcinoma: A Potential Diagnostic Pitfall

Abstract: We report a case of renal metastases from prostate cancer to show that the possibility of tumor metastasis, although rare, should always be considered in the differential diagnosis of renal mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…In addition to our case report only a few cases have been reported for prostate cancer metastasising to the renal system 1315. As kidneys are highly vascular organs, metastatic infiltration is most likely a result of arterial embolisation.…”
Section: Discussionmentioning
confidence: 54%
“…In addition to our case report only a few cases have been reported for prostate cancer metastasising to the renal system 1315. As kidneys are highly vascular organs, metastatic infiltration is most likely a result of arterial embolisation.…”
Section: Discussionmentioning
confidence: 54%
“…[3] In the literature, there is limited number of case reports on renal tumor metastasized from prostate.The first premortem case of renal metastasis was presented by Kutcher et al [4] in 1986, in which diagnosis was made by fine-needle aspiration biopsy. Subsequently, Denti et al [3] reported a renal mass lesion located at left side which was detected by radiological evaluation. Authors performed biopsy from the mass lesion and histopathological examination and immunostaining study revealed prostate adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…[5] To the best of our knowledge from literature searches, this is the second case of renal metastasis from prostatic adenocarcinoma diagnosed ante-mortem by percutaneous fine needle aspiration. Though, unusual sites of prostatic metastases are widely documented in literature from postmortem findings, Gunlusoy et al [1] and Denti et al [6] respectively reported postmortem findings of bilateral and unilateral renal metastases from prostate carcinoma which was initially misdiagnosed as renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%